Sensors: Expanding the Horizon of Mechanochromic Detection by Luminescent Shear Stress Sensor Supraparticles (Adv. Funct. Mater. 19/2019). (7th May 2019) - Wintzheimer, Susanne; Reichstein, Jakob; Wenderoth, Sarah; Hasselmann, Sebastian; Oppmann, Maximilian; Seuffert, Marcel T.; Müller‐Buschbaum, Klaus; Mandel, Karl
Abstract : In article number 1901193, Karl Mandel and co‐workers assemble hierarchical, nanostructured supraparticles from a toolbox of building blocks and show an intense luminescence that is irreversibly quenched upon the influence of shear stress, thus expanding the horizon of traditional mechanochromic sensors.